2012
DOI: 10.1371/journal.pone.0049214
|View full text |Cite
|
Sign up to set email alerts
|

Study of Association of CD40-CD154 Gene Polymorphisms with Disease Susceptibility and Cardiovascular Risk in Spanish Rheumatoid Arthritis Patients

Abstract: ObjectiveRheumatoid arthritis (RA) is a chronic inflammatory disease associated with increased cardiovascular (CV) mortality. Since CD40-CD154 binding has direct consequences on inflammation process initiation, we aimed to replicate previous findings related to disease susceptibility in Spanish RA population. Furthermore, as the major complication in RA disease patients is the development of CV events due to accelerated atherosclerosis, and elevated levels of CD40L/CD154 are present in patients with acute myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 55 publications
4
29
1
Order By: Relevance
“…rs1883832 and rs4810485 distribution of the genotype and allele frequencies (Table 2) did not significantly differ between RA patients and control subjects. Interestingly, the minor allele frequencies of both CD40 genetic variants identified in this study were lower than those reported previously for European and Asian populations (García-Bermúdez et al, 2012;Liu et al, 2012;Lee et al, 2015). In addition, no association with RA was observed under any genetic model.…”
Section: Genotype and Allele Frequencies Of Rs1883832 And Rs4810485 Ccontrasting
confidence: 88%
See 2 more Smart Citations
“…rs1883832 and rs4810485 distribution of the genotype and allele frequencies (Table 2) did not significantly differ between RA patients and control subjects. Interestingly, the minor allele frequencies of both CD40 genetic variants identified in this study were lower than those reported previously for European and Asian populations (García-Bermúdez et al, 2012;Liu et al, 2012;Lee et al, 2015). In addition, no association with RA was observed under any genetic model.…”
Section: Genotype and Allele Frequencies Of Rs1883832 And Rs4810485 Ccontrasting
confidence: 88%
“…Two functional single nucleotide polymorphisms (SNPs) in the CD40 gene, rs1883832 and rs4810485, which are in strong linkage disequilibrium (r 2 = 0.95), have been previously associated with RA in European populations (Raychaudhuri et al, 2008;Orozco et al, 2010;García-Bermúdez et al, 2012;Lee et al, 2015). The former is located at position -1 in the Kozak sequence, and it has been proposed that the major allele of this SNP enhances the efficiency of CD40 mRNA translation, resulting in up to 32% more CD40 protein (Jacobson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype and allele distributions of the selected CD40 SNPs in healthy control individuals were consistent with previously published data, indicating that our PCR-ASRA technique generates appropriate genotyping results [21][22][23]. In addition, 10% of the samples were regenotyped by direct sequencing.…”
Section: Resultssupporting
confidence: 86%
“…Further, inflammatory disorders, characterized by high levels of CRP, can develop a secondary immune cell activation, which may result in atherogenesis [54]. In addition, studies have demonstrated that inflammatory related markers such as lipoproteins, ox-LDLs [55], NO [55], TNF-a [56], RANKL [57], CD40L [58], IL-18 [59], MMP-9 [60], MCP-1 [61], insulin [45], EPCs [51] in atherosclerosis are altered in patients with RA. These evidences thus support the theory that systemic inflammation plays a crucial role in the pathogenesis of CVD in patients with RA.…”
Section: Chronic Inflammation and Immune Dysregulation Of Ra And Athementioning
confidence: 99%